Research of opportunities for adaptation and use of international typologies in financial monitoring system of Ukraine - Акімова, Олена Володимирівна (Technology audit and production reserves, 2016)
This article examines some elements of the mechanism for combating anti-money laundering and terrorism financing by the means of typological studies developed by international organizations. International standards for combating anti-money laundering and terrorism financing lay the foundations of legal support and national regimes in this area and provide an effective mechanism for verification of their implementation. Problems of combating legalization (laundering) of proceeds from crime today is particularly important both for Ukraine and for the world, and social danger of this phenomenon in the last decade gained new dimensions, showing its strong connection with the terrorism financing. The legalization of criminal proceeds acquired such proportions that can be a source of financial and economic perturbations for any state and even individual regions. Therefore, any tools that combating these crimes are used in the system of state control. The problems of the structure and functions are defined for international organizations that conduct research for prevention and combating legalization (laundering) of proceeds from crime, terrorism and proliferation of weapons of mass destruction financing. The typologies of the use of cash funds and financial instruments of unlawful activities are considered and signs of such suspicious transactions are revealed for Ukrainian financial sector. It is concluded about the need to analyze the current legislation and to estimate the adequacy of measures for preventing and combating legalization (laundering) of proceeds from crime and, if necessary, to consider their amendments, including with the new FATF recommendations. SWOT-analysis of the typological studies is conducted. It makes it possible to evaluate the possibilities and advantages of their use in the system of financial monitoring.